2012
DOI: 10.1093/deafed/ens014
|View full text |Cite
|
Sign up to set email alerts
|

A National Perspective on Teachers' Efficacy Beliefs in Deaf Education

Abstract: Teachers' sense of efficacy, or the belief that teachers have of their capacity to make an impact on students' performance, is an unexplored construct in deaf education research. This study included data from 296 respondents to examine the relationship of teacher and school characteristics with teachers' sense of efficacy in 80 different deaf education settings in the US. Deaf education teachers reported high overall efficacy beliefs but significantly lower efficacy beliefs in the area of student engagement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
2
16
0
2
Order By: Relevance
“…The teacher for SDHH in this study wanted to help the students in the classroom as much as possible yet felt worried for her students covering the same material again these beliefs are in line with another study that found high overall efficacy beliefs in instructional strategies and classroom management and significantly lower efficacy beliefs in the area of student engagement [67].…”
Section: Discussionsupporting
confidence: 79%
“…The teacher for SDHH in this study wanted to help the students in the classroom as much as possible yet felt worried for her students covering the same material again these beliefs are in line with another study that found high overall efficacy beliefs in instructional strategies and classroom management and significantly lower efficacy beliefs in the area of student engagement [67].…”
Section: Discussionsupporting
confidence: 79%
“…Garberoglio, Gobble, and Cawthon [49] (p. 378) reported that teacher training and school settings might prioritize "instructional strategies and classroom management over student engagement." However, scholars argue that the most important learning (i.e., most likely to convey flexible understanding) occurs when learners engage in solving tasks that pose challenges [2][3][4][5][6][7][8]50].…”
Section: Discussionmentioning
confidence: 99%
“…Sign language allows the deaf to interpret and produce words, phrases, and texts of the written language assuming a role similar to that played by oral communication when it comes to the appropriation of the written message by the listener in Brazil [1], China [23], Australia [24], United States [25], Netherlands [26], and Turkey [27] among other countries.…”
Section: Discussionmentioning
confidence: 99%